(untitled) (The Research of Medical Science Review, 2025)
OBJECTIVE: To determine the outcome of percutaneous nephrolithotomy under spinal versus general anesthesia. METHODOLOGY: This randomized control trial study was planned to be conducted in the year 2024 within the Urology Department of Jinnah Postgraduate Medical Centre (JPMC), Karachi, involving a cohort of 60 patients diagnosed with percutaneous nephrolithotomy, with 30 individuals allocated to either general anesthesia (Group A) or spinal anesthesia (Group B). Eligible participants, who are aged between 16 and 65 years, regardless of gender, possessing an ASA physical status of I or II, having renal calculi exceeding 2 cm in size, and exhibiting a negative urine culture, were included for the purpose of evaluating the primary outcome. The data were subjected to rigorous analysis utilizing SPSS version 26, which encompassed both descriptive statistical methodologies and the statistical test of significance with threshold set at P ≤ 0.05. RESULTS: Among a cohort of 60 patients, undergoing PCNL, the average age was recorded for general anaesthesia at 42.60 ± 18.01 and 40.27 ± 16.62 years for spinal anaesthesia, with 19 individuals (63.3%) and 16 individuals (53.3%) identified as males in both groups, respectively. The significant association was noted in pre op Hb level (p=0.044), Hb level at 24 hours (p=0.018), analgesic requirement (p=0.0001), pain score at 2 hours (p=0.0001), and pain score at 6 hours (p=0.0001) while nonsignificant association was found in Hb level at 6 hours (p=0.456), pain score at 12 hours (p=0.077), pain score at 18 hours (p=0.421), and pain score at 24 hours (p=0.400). CONCLUSION: This investigation elucidates that spinal anesthesia serves as a feasible substitute for general anesthesia in the context of percutaneous nephrolithotomy, offering enhanced early postoperative analgesia and markedly reduced analgesic necessities. Both anesthetic modalities exhibited analogous safety profiles. These results advocate for the incorporation of spinal anesthesia into clinical practice for patients undergoing PCNL who are appropriately selected.